Downregulation of connexin40 is associated with coronary endothelial cell dysfunction in streptozotocin-induced diabetic mice - Makino, Ayako (American Physiological Society, 2008)
Vascular endothelial cells (ECs) play a major role in regulating vascular tone and in revascularization. There is increasing evidence showing endothelial dysfunction in diabetes, although little is known about the contribution of connexins (Cxs) to vascular complications in the diabetic heart. This study was designed to investigate the role of Cxs in coronary endothelial dysfunction in diabetic mice. Coronary ECs isolated from diabetic mice exhibit lowered protein levels of Cx37 and Cx40 (but not Cx43) and a loss of gap junction intercellular communication (GJIC). Vasodilatation induced by the assumed contribution of EC-dependent hyperpolarization was significantly reduced in the diabetic coronary artery (CA). Cx40-specific inhibitory peptide (40)GAP27 strongly attenuated endothelium-dependent relaxation in diabetic CA at the concentration that does not affect the relaxation in control CA, suggesting that the total amount of Cx40 is lower in diabetic CA than in control CA. In diabetic mice, coronary capillary density was significantly decreased in vivo. In vitro, GJIC inhibitor attenuated the ability of EC capillary network formation. High-glucose treatment caused a decrease in Cx40 protein expression in ECs and impaired endothelial capillary network formation, which was restored by Cx40 overexpression. Furthermore, we found that the hyperglycemia-induced decrease in Cx40 was associated with inhibited protein expression of Sp1, a transcriptional factor that regulates Cx40 expression. These data suggest that downregulation of Cx40 protein expression and resultant inhibition of GJIC contribute to coronary vascular dysfunction in diabetes.